What does inclusive sexual and reproductive healthcare look like for bisexual, pansexual and queer women? Findings from an exploratory study from Tasmania, Australia. Issue 3 (3rd March 2020) - Grant, Ruby; Nash, Meredith; Hansen, Emily
Abstract: Increased awareness of the health disparities faced by lesbian, gay, bisexual, transgender, intersex and queer (LGBTIQ) people has driven the need for LGBTIQ-inclusive medical practices internationally. However, despite bisexual, pansexual and queer women's increased sexual health risks and reduced engagement with health services, there is little qualitative research examining their healthcare experiences. In addition, healthcare practitioners continue to report lack of awareness and competence in inclusive practice, particularly regarding these groups. To address these gaps in the literature and practice, this study draws on 21 qualitative interviews with women and general practitioners, comparing and contrasting their understandings and experiences of inclusive sexual and reproductive healthcare. Findings reveal that women value practitioners who take a non-judgemental approach, use inclusive language and are knowledgeable or willing to self-educate about LGBTIQ issues. Practitioners describe prioritising visual indicators of inclusivity, using inclusive language and embracing professional development. However, women and doctors both identify knowledge gaps among healthcare providers and the need for additional training opportunities to support effective inclusive practice.